Adaptive peer-to-peer streaming over hybrid wireless networks. (29th June 2007) - He, Yifeng; Stimpson, Brad; Lee, Ivan; Gu, Xijia; , Ling Guan
In this paper, we propose a centralised Peer-to-Peer (P2P) streaming over hybrid wireless networks to mitigate the congestion at the Access Point (AP) in Wireless Local Area Networks (WLANs). In our proposed architecture, an adaptive receiver-driven mechanism is used to coordinate the streaming from multiple senders. We also propose a peer handoff scheme and an AP handoff scheme for video streaming over hybrid wireless networks. The simulation results show that (1) centralised P2P video streaming over a hybrid wireless network can achieve a much better quality compared to traditional WLAN deployment with heavy background traffic, (2) the adaptive receiver-driven mechanism can synchronise packet delivery from multiple senders, thus increasing streaming quality, (3) the peer handoff scheme enables the receiver to maintain a high aggregate throughput from multiple serving-peers and (4) the AP handoff scheme enables the receiver to roam freely through different cells, while maintaining continuous video streaming.